(610) Theoretical Problems of Industrial Planning- Part II -The System of Industrial Planning المشكلات النظرية للتخطيط الصناعي - الجزء الثاني - نظام التخطيط الصناعي - Linsel, H.; Sack, K. (معهد التخطيط القومى, 2024)
The study examines the industrial planning system through four main axes. It begins by exploring the theoretical framework of a perfectly centralized planning system, where resources and economic decisions are fully controlled by the state. Next, it discusses the theoretical model of an ideal market system in planning and management, emphasizing free market mechanisms based on supply and demand. It then evaluates the practical planning methods employed in European socialist countries, focusing on challenges and achievements. Finally, the study offers insights into planning systems in developing countries, considering their economic and social contexts. The research is supported by practical observations and explanatory footnotes